Justice in solar energy development. (April 2021) - Heffron, R.; Halbrügge, Stephanie; Körner, Marc-Fabian; Obeng-Darko, Nana A.; Sumarno, Theresia; Wagner, Jonathan; Weibelzahl, Martin
Highlights: Solar energy development has positive justice impacts for the energy system. Reformulating legislation to achieve legal certainty can increase solar investment. Flexibility justice can increase economic welfare from solar energy development. Indonesian reform can realise solar energy potential and deliver energy justice. Abstract: To achieve national energy and climate targets across the world, there is a key focus on solar energy development. It is clear from literature that many countries have enormous, under-utilised potentials for solar energy, which can significantly change their energy mix and contribute to the low-carbon ambitions they signed up to under the 2015 Paris Agreement. Our research highlights that there are benefits to solar energy development from a law and economic perspective that are still underexplored. These benefits centre on justice and on how solar energy increases justice within the energy system. From a legal perspective, we review 72 countries and their introduction of energy law with respect to solar energy development. Our analysis illustrates that in some developing countries (new) legislation was not associated with a significant increase in the share of solar energy in the energy mix. We then highlight how to achieve solar energy development through law that can provide certainty for investment. Furthermore, we stress the importance of flexibility that allows the full potential of solar energy to be realised within the energy system. The corresponding form of flexibility justice, combining law and economics, can contribute to increased economic welfare based on market reforms that centre on new market design and market access, while ensuring that it keeps pace with ongoing developments in technology, cost, and ownership.